Reproducibility and validity of adapted clinical tests for the assessment of muscle strength in community-dwelling older adults living with Alzheimer’s disease - Marcos Paulo Braz de Oliveira; Letícia Bojikian Calixtre; Natália Oiring de Castro Cezar; Carla Lima-Truax; Brendon David Truax; Anielle Cristhine de Medeiros Takahashi; Tatiana de Oliveira Sato; Paulo Henrique Silva Pelicioni; Paula Regina Mendes da Silva Serrão; Larissa Pires de Andrade (BMC Geriatrics)
Abstract Background Older adults living with Alzheimer’s disease (AD) have impaired executive functions and can therefore have greater difficulty following the instructions of assessment tests. Therefore, the objective of this study was to determine the intra- and inter-rater reliability and criterion validity of the adapted Five-Times Sit-to-Stand (5STS), 30-Second Sit-to-Stand (30STS) and Calf-Rise Senior (CRS) tests for the assessment of lower limb muscle strength in older adults living with AD. Methods A methodological study was conducted. For the adaptation of the 5STS, 30STS and CRS tests, standardized verbal commands were added during the execution to assist the older adults in beginning and ending the tests (5STS and 30STS: “stand up” and “sit down”; CRS: “stand on your tip toes” and “now you can get down”). Reliability was determined using the intraclass correlation coefficient (ICC3,1), standard error of measurement (SEM) and minimal detectable change (MDC95). Criterion validity of the adapted tests was tested by the correlation with isokinetic measures of the knee and ankle using Spearman’s correlation. Results Forty-two older adults living with AD were included (Mild-AD: 22; Moderate-AD: 20). Intra- and inter-rater reliability were moderate (ICC3,1: 5STS: 0.60, 0.50; 30STS: 0.55; CRS: 0.68, 0.65), with the exception of inter-rater reliability of the 30STS test which was low (ICC3,1: 0.32). Intra-rater SEM and MDC95 (SEM: 5STS: 3.59, 8.33; 30STS: 0.85, 1.97; CRS: 1.37, 3.18) were lower compared to inter-rater values (MDC95: 5STS: 4.02, 9.32; 30STS: 1.42, 3.29; CRS: 1.76, 4.08). The adapted tests correlated significantly with peak torque, average peak torque and total work of the knee (5STS: extensors and flexors [60°/s] [r: -0.33 to -0.46]; 30STS: flexors [180°/s] [r: 0.31 to 0.61]) and ankle (CRS: plantar flexors and dorsiflexors [total work] [30°/s] [r: 0.32 to 0.37]). Conclusion The adapted 5STS, 30STS and CRS tests demonstrated moderate reliability and correlated with maximum lower limb muscle strength and endurance in older adults living with AD.